Penentuan Plumbum Menggunakan Kaedah Analisis Suntikan Aliran Berdasarkan Pembentukan Kompleks antara Plumbum dengan Reagen Galosianin - Yusof, Nor Azah; Ahmad, Musa (Universiti Putra Malaysia Press, 2002)
Flow injection analysis (FIA) with UV-Visible detection has been used in this study for Pb(II) detection in an aqueous environment. The FIA system used in this study was based on the reaction between Pb (II) and gallocyanine which formed a complex with maximum absorbance at around 550 nm. The carrier solution flow rate, solution pH and the reagent concentration have been optimised to increase the efficiency of the FIA system. The FIA system was found to be optimum at 1.2 mL/min flow rate and pH 8. The dynamic range for the Pb(II) concentration was found to be between 1.0 x 1([3 mg/L and 1.0 x lOt mg/L. The reproducibility of the method was very good with RSD value of 1.03 %. At mole ratio of 1:1, Cd(II) , Ni(II) and Co(II) were found to interfere with respective relative error of 10.05 %, 10.15 % and 10.25 %.